Surgical Repair of Congenital Submitral Left Ventricular Aneurysm - Faisal K. AlGhamdi, MBBS; Mustafa Mohammed Barakat, MD; Abdulaziz Al-Khaldi, MD (Annals of Thoracic Surgery Short Reports)
Left ventricular aneurysm is a rare abnormality of the left ventricle. It has many etiologies, such as coronary artery disease or infection, and it can be congenital. It occurs in multiple locations; one location is beneath the mitral valve annulus, submitral left ventricular aneurysm. We report a case of a 10-year-old girl who presented with severe mitral regurgitation and was found to have congenital left ventricular aneurysm, which was repaired surgically.